HOPE FAMILY EFFECTIVENESS PROGRAM (PKH) IN THE VILLAGE KEDUNGBANTENG KEDUNGBANTENG SUB-DISTRICT BANYUMAS DISTRICT - Ani Fitriyani; Andri Trianfano; Taufik Purboyo (Department of Public Administration, University Wijaykusuma Purwokerto, 2023)
This study entitled The Effectiveness of the Family Hope Program (PKH) in Kedungbanteng Village, Kedungbanteng District, Banyumas Regency. This study aims to describe and analyze the Effectiveness of the Family Hope Program (PKH) in Kedungbanteng Village, Kedungbanteng District, Banyumas Regency and find out what factors support and what factors hinder the Family Hope Program (PKH) in Kedungbanteng Village, Kedungbanteng District, Banyumas Regency. The research method used is descriptive qualitative. Determination of informants using purposive sampling method, and analysis of research results using an interactive model. The summary of this research are:. 1. Aspect of success achieved by the program, the implementation of PKH is good and those who are directly involved are PKH facilitators and PKH KPM. PKH facilitators have provided assistance to PKH KPM well. In the implementation of socialization, companions use the film screening method in order to provide an understanding of KPM. During the disbursement process, the assistance funds received by KPM are in accordance with the stipulated provisions, but there is a discount for administrative fees of Rp. 5000 to Rp. 10,000 per KPM and for KPMs it is not allowed to withdraw money at ATMs independently. 2. Aspect is targeting accuracy, each recipient of PKH social assistance has met the specified component criteria. However, there are still many economically disadvantaged communities who do not receive PKH social assistance, especially the elderly. This is due to the absence of re-collection and direct field inspection to ensure that the prospective KPM is not economically capable and only uses data from the central party which in fact must be re-checked for correctness. 3. Aspect is satisfaction with the program, PKH facilitators have worked well and are responsible for KPM. The assistant can direct the KPM in the implementation of PKH and can provide solutions to the KPM if there are obstacles in the implementation of the PKH. 4. Aspect of input and output, in the data validation process to determine candidates for KPM PKH only uses the Integrated Social Welfare Data from 2013 to the present. Therefore, there is a problem that many people do not receive the PKH social assistance. 5. Aspect is the overall achievement of goals, most of the community is ready to be graduated from PKH social assistance if they are considered economically capable. The community feels very helped by the PKH social assistance and the community feels the real benefits obtained from PKH social assistance such as being able to pay school fees for children, the nutritional needs of toddlers. The implications used to increase the effectiveness of the Family Hope Program (PKH) in Kedungbanteng Village, Kedungbanteng District, Banyumas Regency are as follows. 1. For beneficiary families, should be able to use the assistance provided properly in accordance with the provisions. It is hoped that you will always attend the socialization gathering which is held once a month in order to understand the contents of the socialization and so that you can be moved to volunteer to give up PKH social assistance if you are considered economically capable. xvii 2. For PKH administrators and assistants, namely all implementing parties involved in the implementation of PKH, they must carry out socialization as often as possible so that the community knows and knows the purpose of PKH, and it is hoped that people who already feel capable can be willing to release and give up PKH social assistance. Prior to determining a candidate for a KPM PKH, a visit and a review of the prospective KPM PKH home must be carried out which is registered from the DTKS data to ensure that PKH social assistance can be provided to the right KPM. Do not use old data and must use current data in accordance with data generated from field observations. 3. For the Social Service, namely updating of data in determining KPM candidates is carried out annually on a regular basis so that people who have not received assistance funds can be registered as PKH KPM and people who are considered capable can be graduated from the Family Hope Program (PKH) social assistance.